Metabolism in compensatory growth. V. Effect of undegraded protein in compensatory growth - Mahyudin, Prappti (Indonesian Animal Sciences Society, 2001)
An experiment was designed to study the effect of increasing availability of amino acids in growing animal fed maintenance diet and which previously subjected to underfeeding. Twelve wether Iambs were divided into 3 treatment groups, each was fed pelleted lucerne (Medicago sativa). The treatments were: diet at maintenance energy level (M), M + 60 g formaldehyde treatedcasein(M + HCHO-casein) and ad libitum. The increase in protein consumption increased nitrogen (N) retention, although the highest efficiency of N retention occurred in animal fed M diet (0.36) compared to those fed M + HCHO-casein (0.31) or ad libitum diet (0.2). Provision of amino acids by supplementation of 60 g HCHO-casein resulted in an increment of 19 g glucose/d or 32 g glucose/lOO g protein. Glucose entry rate (GER) increased with increasing digestible crude protein. Although GER was not different between animals on M and M + HCHO-casein diet, the uptake of glucose in the hind-limb muscles of animals on the M + HCHO-casein was twice (0. 18mM) than that of animals on the M diet (0.08 mM). There was a significant effect on the uptake and output of essential amino acids, leucine, isoleucine, lysine and threonine and non-essential amino acids, tyrosine and glutamine as levels of protein in the diet increased. Supplementation with HCHO-casein increased the arterial blood concentration of branch chain amino acids (BCAA) by 76 % and phenylalanine by 61 %. In general there was an increase in the arterial concentration of amino acids in animals fed either M + HCHO-casein or ad libitum. However, this increase was followed by increased amino acids oxidation, which showed in increased urea excretion. There was a positive correlation between urinary urea and N intake, suggesting that amino acids were not fully utilized for protein synthesis or protein deposition. Â Key words: Compensatory growth, amino acid, N retension